1982
DOI: 10.1002/1097-0142(19821015)50:8<1587::aid-cncr2820500820>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy findings in squamous-cell carcinoma of the esophagus

Abstract: The findings at autopsy of 79 patients with esophageal carcinoma over a period of 15 years were reviewed. Five patients were free of tumor, and another seven had disease localized to the esophagus and other mediastinal structures. Sixty‐seven (85%) had metastatic disease. The average number of metastatic sites per patient was 3.3. Most common metastatic sites were lymph nodes (73%), lung (52%), and liver (47%). The patients in this series had a higher incidence of metastases than those in other published serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(45 citation statements)
references
References 8 publications
4
38
1
2
Order By: Relevance
“…They also analyzed macroscopic tumors unlike ours. Anderson and Lad (1982) described that the doubling time of squamous-cell carcinoma was calculated to be 48 to 70 days and it would take 4.5 years for few tumor cells to be a detectable one. The prognostic difference of subclinical tumors seems to become apparent not immediately but several years later.…”
Section: Discussionmentioning
confidence: 99%
“…They also analyzed macroscopic tumors unlike ours. Anderson and Lad (1982) described that the doubling time of squamous-cell carcinoma was calculated to be 48 to 70 days and it would take 4.5 years for few tumor cells to be a detectable one. The prognostic difference of subclinical tumors seems to become apparent not immediately but several years later.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of surgical selection is also illustrated by the high proportion of tumours within the lower third of the oesophagus. Post-mortem studies record squamous cell carcinoma as being most common in the middle third (Anderson & Lad, 1982) but the lower third tumours are more amenable to surgical treatment (Skinner, 1976) and have therefore been found to have a better prognosis (Miller, 1962). This trend was confirmed in this study with patients surviving longer who had tumours sited in the lower third versus upper and middle thirds.…”
Section: Discussionmentioning
confidence: 99%
“…10 Therefore, the diagnosis of renal metastases is very difficult, particularly in patients with esophageal cancer, and is often established accidentally on surveillance exams. Although previous study based on autopsy findings showed that 13% of esophageal cancer had metastatic lesions in the kidney, 11 such cases are rarely encountered in the clinical practice because they are asymptomatic. The present case in addition to the other 11 previously reported cases of esophageal cancer with renal metastasis and their treatment are briefly summarized in Table 1.…”
Section: Discussionmentioning
confidence: 95%